APLIKASI JENIS PUPUK ORGANIK DAN DOSIS PUPUK KCL PADA TANAMAN UBI JALAR - Hadi Sulkan; Ernita Ernita; T Rosmawaty (UIR Press, 2014)
The purpose of this research was to examine the effect of organic fertilizer and KCl dosage on crop yields of sweet potato. The research was conducted at the experimental farm of Faculty of Agriculture Riau Islamic University Pekanbaru from December 2013 to April 2014. The research used a completely randomized design (CRD) with 4 x 4 factorial and three replications. The first factor was the type of organic fertilizer (P) which consisted of 4 levels i.e., without organic fertilizer, compost palm oil, chicken manure and cow manure. The second factor was the dosage of KCl (K) which consisted of 4 levels, i.e., without KCl, KCl with dosage of 7.5 g/ridges (150 kg/ha), KCL with dosage of 15 g/ridges (300 kg/ha) and KCL with dosage of 22.5 g/ridges (450 kg/ha). The data were statistically analyzed by F-test and further HSD at the 5% at the significant level. The interaction between the type of organic fertilizer and KCl dosage had no significant effect on all parameters observed. Furthermore, the type of organic fertilizer affected significantly on tuber weight per tuber and tuber production per ridge. The best treatment used chicken manure. KCl had a significant effect on the number of tubers per plant, tuber weight per tuber, tuber weight per plant, and tuber production per mound. The best treatment was 22.5 g KCl per mound (450 kg/ha).